The search for interdisciplinarity in the disciplines of architectural design in the undergraduate program in architecture and urbanism - Djanine Dolovet Martins; Adriana Aparecida de Lima Terçariol (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This article represents the final work of the Post - Graduation Course: "Specialization in Teaching and Learning Assessment", offered at a University of private network in the municipality of Presidente Prudente / SP. The purpose of this paper is to present how the discipline of Architectural Design, specifically, the course of Architecture and Urbanism offered by that university, needs and depends on an interdisciplinary organization, involving all disciplines of the curriculum of the course grade. To develop this study, we chose to bibliographic and documentary research and research methodology. In literature the main works were consulted: Farm (1999, 1979), Morin (2007), Japiassu (1976), Luck (2001), Freire (2009). By analyzing the documents was adopted as reference the pedagogical project of the Architecture and Urbanism Course and guidelines support the structuring of undergraduate projects in Architecture and Urbanism area. As main results, it was concluded that the discipline of Architectural Design needs this interdisciplinary, involving all other course subjects because a Architectural Design also depends on a whole learning about different areas to achieve them.